Chromophore chemistry of fluorescent proteins controlled by light - Shcherbakova, Daria M. (2014)
Recent progress in molecular engineering of genetically-encoded probes whose spectral properties are controlled with light, such as photoactivatable, photoswitchable and reversibly switchable fluorescent proteins, have brought the new possibilities to bioimaging and super-resolution microscopy. The development of modern photoconvertible proteins is linked to the studies of light-induced chromophore transformations. Here, we summarize the current view on the chromophore chemistry in the photocontrollable fluorescent proteins. We describe both the fundamental principles and specific molecular mechanisms underlying the irreversible and reversible chromophore photoconversions. We discuss advancements in super-resolution microscopy that became possible due to the new protein phenotypes and understanding of their chromophore transformations.